Tabuik Ritual in Pariaman: Islamic Acculturation and Local Culture through the Perspective of al-'Urf - Kumaidi Kumaidi; Rahmat Hidayat; Hardiansyah Padli; Jamilus Jamilus; Arna Saskia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study examines the acculturation between Islamic values and Minangkabau local culture in the Tabuik ritual in Pariaman through the perspective of al-'urf in usul al-fiqh. Historically rooted in the Shia tradition, the Tabuik ritual has undergone transformation along three dimensions, namely theological, social-functional, and symbolic, since the nineteenth century, developing into a cultural identity of the Sunni community in Pariaman. Theologically, its grounding in martyrdom has been reframed as a moral commemoration of resistance to injustice. Socially, a minority sectarian practice has developed into a community-wide tradition emphasizing solidarity, mutual cooperation, and gotong royong. Symbolically, the replica of Husain's tomb has been reconstituted as an icon of communal identity. This study employs a narrative literature review with a qualitative approach to analyze the elements of the Tabuik ritual based on the classification of urf sahih and urf fasid and assess the legitimacy of its practices under Islamic law. The findings indicate that the social dimensions of the ritual, including communal solidarity, mutual cooperation, and collective identity, can be categorized as urf sahih because they support the objectives of maqasid al-shariah. Conversely, practices involving beliefs in material blessings or supernatural powers with ritual objects tend to fall within urf fasid because they may conflict with the principle of tawhid. The discourse between puritan and cultural groups reflects tensions over Tabuik. This study contributes to understanding the flexibility of Islamic law in accommodating cultural diversity through selective and normative evaluation.